Discovery of dimethyl pent-4-ynoic acid derivatives, as potent and orally bioavailable DGAT1 inhibitors that suppress body weight in diet-induced mouse obesity model. Issue 10 (1st June 2018) - Yu, Tao; Wu, Chengde; Shih, NengYang; Li, Qi; Chan, Chichung; Pan, He; Yao, Dan; Pan, Yan; Liang, Wei; Shen, Liang; Zhao, Hui; Li, Jian; et al.
Graphical abstract: Highlights: We have described a novel class of orally bioavailable DGAT1 inhibitors. We introduced alkyne to replace cyclohexane ring as linker in drug design. One of the desired compound 29 exhibited superior efficacy in DIO animal model. Abstract: Diacylglycerol acyltransferase (DGAT) is expressed abundantly in intestine, liver, and adipose tissues. DGAT1 is the crucial and rate-limiting enzyme that mediates the final step in triacylglycerol (TAG) resynthesis during dietary fat absorption. However, too much triacylglycerol (TAG) reserve will lead to genetic obesity (Hubert et al., 2000). DGAT1 knockout mice could survive and displayed a reduction in the postprandial rise of plasma TG, and increased sensitivity of insulin and leptin. Here we report the discovery and characterization of a novel selective DGAT1 inhibitor 29 to potentially treat obesity. Compound 29 showed lipid lowering effect in mouse lipid tolerance test (LTT) and also reduced body weight in DIO mice without observable liver damage.